Preparation method of composite positive electrode
Through wet mixing and heat treatment technology of alcohol solvents, the problem of moisture influence of high-nickel positive electrode materials and halide solid electrolytes during sintering is solved, forming a composite positive electrode with a uniform core-shell structure, improving electrochemical performance and capacitance, and reducing the Energy consumption and cost.
Patent Information
- Application Number
- CN202311351916.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2023-10-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when the high nickel positive electrode material and the halide solid electrolyte are mixed and sintered to form a composite positive electrode, moisture has a negative impact on electrical properties, resulting in a decrease in electrical properties, and it is difficult to take into account both the mechanical properties and thickness control of the solid electrolyte.
The alcohol solvent is used to mix wet to form a slurry, and the composite positive electrode is formed through heat treatment, so as to realize the in-situ synthesis of solid electrolyte on the surface of the positive electrode material, forming a uniform core-shell structure, avoiding the influence of moisture, and rolling through anti-sticking carrier Press-forming to reduce energy consumption.
It improves the solid dispersion and electrochemical properties of the composite positive electrode, reduces the degree of unhealthy phase, improves the capacitance and cycling performance, saves manufacturing costs and has environmental benefits.
Smart Images

Figure CN119314997A_ABST
Abstract
Description
Technical Field
[0001] This case is about a method for preparing battery electrodes, in particular, a method for preparing a composite positive electrode, which uses an alcohol solvent to obtain a solid electrolyte coating to improve electrical performance. Background Art
[0002] Considering safety and energy density, the development of solid-state batteries has become a mainstream trend in recent years. Compared with traditional lithium batteries, solid-state batteries still have room for improvement in various aspects. In terms of positive electrode materials, high-nickel positive electrode materials have the defect of being highly sensitive to moisture; in terms of solid electrolytes, how to reduce their thickness while improving mechanical properties is also a challenging issue.
[0003] Among all types of solid electrolytes, the types with the greatest potential for mass production are oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes. Among them, halide solid electrolytes have the characteristics of high stability, high safety, high ionic conductivity, and low interface impedance, and are one of the materials that have been widely discussed in recent years. However, halide solid electrolytes and high-nickel cathode materials also have the defect of being highly sensitive to moisture.
[0004] In the existing preparation method, high nickel cathode material and halide solid electrolyte are mixed and then sintered to form a composite cathode. Compared with dry mixing, wet mixing using water as a solvent has a lower manufacturing cost and can obtain a composite cathode with high solid dispersion, but water will have a negative impact on the halide solid electrolyte and high nickel cathode material, thereby reducing the electrical performance of the composite cathode.
[0005] In view of this, it is necessary to provide a method for preparing a composite positive electrode, obtaining a solid electrolyte coating layer through an alcohol solvent, so as to eliminate the negative impact of moisture on the composite positive electrode and improve the electrical performance, thereby solving the deficiencies of the prior art. Summary of the invention
[0006] The objective of this case is to provide a method for preparing a composite cathode. The method for preparing the composite cathode includes the following steps. First, a cathode material, a solid electrolyte, and an alcohol solvent are mixed to form a slurry. Then, the slurry is heat-treated to form a composite cathode. Compared with dry mixing, wet mixing has low cost, is easy to control, and can improve the solid dispersion of the composite cathode. Moreover, the solid electrolyte is dissolved in the alcohol solvent and uniformly mixed with the cathode material, enabling in-situ synthesis on the surface of the cathode material particles during subsequent heat treatment, thereby forming composite cathode particles with a uniform core-shell structure and improving the electrochemical performance. Wet mixing with an alcohol solvent can also avoid the negative impact of moisture on the composite cathode, resulting in a composite cathode with low impurity phases. Before heat treatment, the slurry is, for example, coated on a carrier and roll-pressed into shape. The carrier is, for example, an anti-sticking film, which is beneficial for peeling after shaping. The slurry is more, for example, coated between two carriers and roll-pressed into shape, and the carriers are an anti-sticking film and a current collector respectively, so that a current collector with a composite cathode can be directly obtained after heat treatment. The temperature of the heat treatment is, for example, between 160°C and 200°C, with low energy consumption, saving manufacturing costs and having environmental benefits.
[0007] To achieve the aforementioned objective, this case provides a method for preparing a composite cathode, including the steps of: (a) providing a cathode material, a solid electrolyte, conductive carbon, and an alcohol solvent, wherein the cathode material includes a plurality of first particles, and the composition of the cathode material is Li[Ni a Co b Mn c Al d O2, a + b + c + d = 1, 0.8 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1, wherein the composition of the solid electrolyte is Li3InCl x F y , and x + y ≤ 6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 3; (b) mixing the cathode material, the solid electrolyte, the conductive carbon, and the alcohol solvent to form a first slurry; (c) mixing the first slurry and a binder to form a second slurry; and (d) heat-treating the second slurry to form a composite cathode, wherein the composite cathode includes a plurality of second particles, and each of the plurality of second particles includes one of the plurality of first particles and the solid electrolyte, and the solid electrolyte coats the one of the plurality of first particles.
[0008] In one embodiment, the particle size of the first particles is between 0.5 μm and 30 μm.
[0009] In one embodiment, the cathode material includes a single-crystalline cathode material.
[0010] In one embodiment, 0.85 < a ≤ 1.
[0011] In one embodiment, the alcohol solvent includes ethanol.
[0012] In one embodiment, the second slurry is heat-treated after being formed.
[0013] In one embodiment, the second slurry is formed on a first carrier, and the first carrier includes a current collector or an anti-adhesion material.
[0014] In one embodiment, the first carrier includes two first carriers, and the second slurry is formed between the two first carriers.
[0015] In one embodiment, the second slurry is heat-treated on a second carrier, and the second carrier includes glass or metal.
[0016] In one embodiment, the temperature of the heat treatment is between 160°C and 200°C.
[0017] In one embodiment, the heat treatment time is between 10 minutes and 180 minutes.
[0018] In one embodiment, the thermal treatment is performed in a non-oxidizing atmosphere.
[0019] In one embodiment, the conductive carbon includes carbon black, carbon nanotube or carbon fiber.
[0020] In one embodiment, the adhesive includes polytetrafluoroethylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of a composite positive electrode preparation method according to an embodiment of the present invention.
[0022] Figure 2A This is the SEM image of the first example of this case.
[0023] Figure 2B This is a SEM image of the first comparative example.
[0024] Figure 3A This is a heat flow rate-temperature curve diagram of the first example of this case.
[0025] Figure 3B 2 is a heat flow rate-temperature curve diagram of the second comparative example.
[0026] Figure 4A This is the X-ray diffraction pattern of the first example of this case.
[0027] Figure 4B is the X-ray diffraction pattern of the second comparative example.
[0028] Figure 5A This is a voltage-capacitance curve diagram of the first example of this case.
[0029] Figure 5B This is a voltage-capacitance curve diagram of the second example of this case.
[0030] Figure 5C This is a voltage-capacitance curve diagram of the third example of the present case.
[0031] Figure 5D is a voltage-capacitance curve diagram of the first comparative example.
[0032] Figure 5E is a voltage-capacitance curve diagram of the second comparative example.
[0033] Fig. 6A This is a capacitance-cycle number curve diagram of the second example of this case.
[0034] Figure 6B This is a capacitance-cycle number curve diagram of the third example of the present case.
[0035] Figure 6C FIG. 4 is a capacitance-cycle number curve of the first comparative example.
[0036] The reference numerals are described as follows:
[0037] S1, S2, S3, S4: Steps DETAILED DESCRIPTION
[0038] Some exemplary embodiments embodying the features and advantages of the present case will be described in detail in the following description. It should be understood that the present case can have various variations in different aspects, all of which do not depart from the scope of the present case, and the descriptions and drawings therein are essentially for illustrative purposes and not for limiting the present case. For example, if the following content of the present case describes a first feature being disposed on or above a second feature, it means that it includes embodiments where the above-mentioned first feature and the above-mentioned second feature are in direct contact, and also includes embodiments where additional features can be disposed between the above-mentioned first feature and the above-mentioned second feature, such that the above-mentioned first feature and the above-mentioned second feature may not be in direct contact. Additionally, it can be understood that although terms such as "first", "second", "third", etc. may be used in the claims to describe different components, these components should not be limited by these terms, and in the embodiments, these components corresponding to the descriptions are represented by different component symbols. These terms are used to distinguish different components. For example, the first component can be referred to as the second component. Similarly, the second component can also be referred to as the first component without departing from the scope of the embodiment. The term "and / or" in the specification includes any and all combinations of one or more of the related listed items. The term "about" refers to an average value within the standard error range that is generally acceptable to those with ordinary knowledge in the art. Unless otherwise specified in the operation / work examples or explicitly stated additionally, all numerical ranges, quantities, numerical values, and percentages (such as angles, time lengths, temperatures, operating conditions, quantity ratios, etc.) disclosed in the present case should be understood to be modified by the term "about" or "substantially" in all embodiments. Therefore, unless otherwise stated, the numerical parameters stated in the present case and the appended claims are approximate values that can vary as needed. For example, the significant digits of each numerical parameter should be interpreted at least by applying the ordinary rounding method. Ranges can be expressed herein as from one endpoint to the other endpoint or between two endpoints. Unless otherwise stated, all ranges disclosed herein include the endpoints.
[0039] Please refer to Figure 1 。 Figure 1 A flowchart of a method for preparing a composite positive electrode according to an embodiment of the present case. In this embodiment, the method for preparing the composite positive electrode includes the following steps. First, as shown in step S1, a positive electrode material, a solid electrolyte, a conductive carbon, and an alcohol solvent are provided. The positive electrode material includes a plurality of first particles. The composition of the positive electrode material is Li[Ni a Co b Mn c Al d O2, and a + b + c + d = 1, 0.8 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1. The composition of the solid electrolyte is Li3InCl x F y, and x+y≤6, 0≤x≤6, 0≤y≤3. In this embodiment, the positive electrode material is, for example, a group consisting of Li[Ni a Co b Mn c ]O2, and a=0.83, b=0.12, c=0.05, that is, the ratio of nickel, cobalt and manganese in the NCM material is 83:12:5. In another embodiment, the positive electrode material is, for example, a group consisting of Li[Ni a Co b Mn c Al d ]O2, and a=0.88, b=0.06, c=0.05, d=0.01. In another embodiment, the positive electrode material can also be, for example, a nickel cobalt manganese oxide (NCM) material or a nickel cobalt manganese aluminum oxide (NCMA) material with a different composition ratio, or a composition of Li[Ni a Co b Al d ]O2 of lithium nickel cobalt aluminum oxide (NCA) material. In some embodiments, the positive electrode material may also be, for example, a lithium nickel oxide composed of LiNiO2. Of course, the present invention is not limited to this. In the present embodiment, the positive electrode material is, for example, a single crystal positive electrode material, and the particle size of the first particle is between 0.5μm and 30μm, so as to achieve the enhancement of the electrochemical performance of the composite positive electrode through the single crystal structure and small particle size. The positive electrode material is, for example, prepared by solid-state synthesis or sol-gel process. It should be noted that the type, particle size, composition ratio and process of the positive electrode material in this case are not limited to this and will not be repeated. In the present embodiment, the alcohol solvent is, for example, ethanol, and therefore has the advantages of being non-toxic, easy to obtain and low cost. In this embodiment, the conductive carbon includes, for example, carbon nanotubes, conductive graphite, conductive carbon black, acetylene black or vapor grown carbon fiber (VGCF), but the present invention is not limited thereto.
[0040] Then, as shown in step S2, the positive electrode material, the solid electrolyte, the conductive carbon and the alcohol solvent are mixed to form a first slurry. Compared with dry mixing, wet mixing is low in cost and easy to control, which can improve the solid dispersion of the composite positive electrode. Furthermore, the solid electrolyte can be synthesized in situ on the surface of the first particle of the positive electrode material, thereby forming a composite positive electrode example with a uniform core-shell structure and improving the electrochemical performance. Since the wet mixing is carried out through an alcohol solvent, the negative effect of moisture on the composite positive electrode can be avoided, resulting in a composite positive electrode with a low impurity phase.
[0041] Furthermore, as shown in step S3, the first slurry and a binder are mixed to form a second slurry. In the present embodiment, the first slurry and the binder are mixed in a non-oxidizing atmosphere, for example, to avoid oxidation. The first slurry and the binder are gradually heated from room temperature to between 70°C and 90°C during mixing, for example, to promote the volatilization of the alcohol solvent to form a viscous second slurry, which is beneficial to the subsequent preparation of the composite positive electrode. In the present embodiment, the binder is, for example, polytetrafluoroethylene (PTFE).
[0042] Finally, as shown in step S4, the second slurry is heat-treated to form a composite positive electrode. The composite positive electrode includes a plurality of second particles. Each of the plurality of second particles includes one of the plurality of first particles and a solid electrolyte, and the solid electrolyte coats the one of the plurality of first particles. Through wet mixing and heat treatment, the solid electrolyte is synthesized in situ on the surface of the first particle of the positive electrode material, thereby forming a second particle of the composite positive electrode having a uniform core-shell structure and improving the electrochemical performance. In this embodiment, the second slurry is heat-treated after forming. The second slurry is, for example, roll-formed on a first carrier or between two first carriers. The first carrier includes a current collector or an anti-adhesion material. In this embodiment, the second slurry is, for example, rolled between two polyvinylidene fluoride (PTFE) films, which is convenient for stripping after rolling and subsequent heat treatment. In another embodiment, the second slurry is roll-formed between an aluminum foil and a polyvinylidene fluoride (PTFE) film, and can be directly formed into a current collector having a composite positive electrode after stripping and heat treatment. In this embodiment, the molded second slurry is, for example, carried on a second carrier for heat treatment. The second carrier includes, for example, a glass or a metal. The temperature of the heat treatment is, for example, between 160°C and 200°C, and the time is between 10 minutes and 180 minutes. Preferably, the temperature of the heat treatment is between 170°C and 190°C. The energy consumption is low, the manufacturing cost is saved and it has environmental benefits. The heat treatment is carried out in a non-oxidizing atmosphere, for example, in an argon atmosphere or a nitrogen atmosphere.
[0043] The following describes the process and effects of the present invention in detail through comparative examples and demonstration examples.
[0044] First example:
[0045] The first example is a composite positive electrode prepared in the following manner. First, a positive electrode material, a solid electrolyte, a conductive carbon and an alcohol solvent are provided. The positive electrode material is a polycrystalline positive electrode material, and its composition is Li[Ni 0.83 Co 0.12 Mn 0.05 ]O2. In other words, the positive electrode material of the first exemplary embodiment is a polycrystalline nickel cobalt manganese oxide material with a molar ratio of nickel, cobalt and manganese of 83:12:5. The composition of the solid electrolyte is Li3InCl6. The conductive carbon is vapor-grown carbon fiber (VGCF). The alcohol solvent is ethanol.
[0046] Next, the positive electrode material, solid electrolyte, conductive carbon and alcohol solvent are mixed and ground to form a first slurry. Furthermore, the first slurry and a binder are mixed to form a second slurry. The binder is polyvinylidene fluoride (PTFE). The first slurry and the binder are mixed in an argon atmosphere, and the temperature is gradually raised from room temperature (25°C) to 80°C during the mixing process to promote the volatilization of ethanol to form a viscous second slurry.
[0047] Then, the second slurry is evenly coated between two polyvinylidene fluoride (PTFE) films and roll-formed. Finally, the second slurry is peeled off from the polyvinylidene fluoride film and heat-treated in a flowing argon atmosphere to form the composite positive electrode of the first example. The heat treatment temperature is 180°C and the time is 120 minutes.
[0048] Second example:
[0049] The preparation method of the second exemplary embodiment is substantially the same as that of the first exemplary embodiment, except that in the second exemplary embodiment, the positive electrode material is a single crystal positive electrode material, and its composition is Li[Ni 0.83 Co 0.12 Mn 0.05 In other words, the positive electrode material of the second exemplary embodiment is a single crystal nickel cobalt manganese oxide material with a molar ratio of nickel, cobalt and manganese of 83:12:5.
[0050] The third example:
[0051] The preparation method of the third example is substantially the same as that of the first example, except that in the third example, the positive electrode material is a polycrystalline positive electrode material, and its composition is Li[Ni 0.88 Co 0.06 Mn 0.06In other words, the positive electrode material of the third exemplary embodiment is a polycrystalline nickel cobalt manganese oxide material having a molar ratio of nickel, cobalt and manganese of 88:6:6.
[0052] First comparative example:
[0053] The first comparative example is a composite positive electrode prepared in the following manner. A positive electrode material, a solid electrolyte, a conductive carbon and a binder are provided. The positive electrode material is a polycrystalline positive electrode material, and its composition is Li[Ni 0.83 Co 0.12 Mn 0.05 ]O2. In other words, the positive electrode material of the first comparative example is a polycrystalline nickel cobalt manganese oxide material with a molar ratio of nickel, cobalt and manganese of 83:12:5. The composition of the solid electrolyte is Li3InCl6. The conductive carbon is vapor grown carbon fiber (VGCF). The binder is polyvinylidene fluoride (PTFE)
[0054] Next, the positive electrode material, the solid electrolyte, the conductive carbon and the binder are mixed and ground, and after heat treatment, a composite positive electrode of the first comparative example is formed.
[0055] Second comparative example:
[0056] The preparation method of the second comparative example is substantially the same as that of the first comparative example, except that deionized water is used as the solvent in the second comparative example.
[0057] Please refer to FIG. 2A to FIG. 2B . Figure 2A This is the SEM image of the first example of this case. Figure 2B This is the SEM image of the first comparative example of this case. Figure 2A as well as Figure 2B As shown, the first exemplary embodiment prepared by wet mixing has significantly higher solid dispersion than the first comparative embodiment prepared by dry mixing, that is, the conductive carbon and the binder are uniformly distributed among the second particles.
[0058] Please refer to FIG. 3A to FIG. 3B . Figure 3A as well as Figure 3B They are heat flow rate-temperature curves of the first exemplary embodiment and the second comparative embodiment of the present invention. Figure 3A as well as Figure 3BThe results were obtained by performing a differential scanning calorimetry (DSC) on the first example and the second comparative example of the present case. As shown in the figure, the first example of wet mixing using an alcohol solvent showed a change in heat flow rate at around 180°C. In contrast, the second comparative example of wet mixing using water showed a change in heat flow rate at around 220°C. In other words, the slurry obtained by wet mixing using an alcohol solvent can be heat treated at a lower temperature to produce a composite positive electrode, thereby reducing energy consumption and saving manufacturing costs. Furthermore, in Figure 3A In the first exemplary embodiment of the present invention, the peak value of the reaction temperature is 180° C., and the peak width is 20° C. Therefore, it can be seen that the temperature of the heat treatment in the present invention is preferably between 170° C. and 190° C.
[0059] Please refer to FIG. 4A to FIG. 4B . Figure 4A as well as Figure 4B 1 and 2 are X-ray diffraction patterns of the first exemplary embodiment and the second comparative embodiment of the present invention. Figure 4A as well as Figure 4B The X-ray diffraction analysis was performed on the first example and the second comparative example at 180°C for 60 minutes. Figure 4A as well as Figure 4B By comparison, it can be clearly found that the X-ray diffraction spectrum of the second comparative example has diffraction peaks of the (222) plane, (440) plane and (622) plane of indium oxide (In2O3), and the diffraction peak of the (101) plane of lithium chloride (LiCl). In other words, wet mixing with water as a solvent will result in a large amount of indium oxide and lithium chloride impurities in the prepared composite positive electrode. In contrast, the composite positive electrode prepared by wet mixing with alcohol solvents has a low degree of impurities.
[0060] Please refer to FIG. 5A to FIG. 5E . FIG. 5A to FIG. 5C The voltage-capacity curves are obtained by testing the button batteries made in the first, second and third examples of the present invention. Figure 5D as well as Figure 5EThe voltage-capacity curves are obtained by testing the button batteries made in the first comparative example and the second comparative example respectively. The positive electrode of the button battery is the composite positive electrode of the first example, the second example, the third example, the first comparative example and the second comparative example, and the negative electrode is lithium metal. The voltage window is 2.5V to 4.4V, the charge and discharge rate (C-rate) is 0.1C, and it is charged in constant current (CC) mode and discharged in constant current constant voltage (CCCV) mode. The constant current constant voltage discharge method is to maintain the current constant during the discharge process, and then maintain the voltage constant until the discharge is completed after reaching the upper limit voltage. The temperature condition of the charge and discharge test is 55°C. FIG. 5A to FIG. 5E As shown, the discharge capacity of the first example is 176 mAh / g, the discharge capacity of the second example is 193 mAh / g, the discharge capacity of the third example is 204 mAh / g, the discharge capacity of the first comparative example is 67.9 mAh / g, and the discharge capacity of the second comparative example is 44.4 mAh / g. It can be seen that compared with the composite positive electrode prepared by dry mixing or wet mixing with water, the composite positive electrode prepared by wet mixing with alcohol solvents has a higher capacitance performance. In addition, the single crystal Li[Ni 0.83 Co 0.12 Mn 0.05 The discharge capacity of the second example of O2 is significantly greater than that of polycrystalline Li[Ni 0.83 Co 0.12 Mn 0.05 ] The first example of O2. In other words, the single crystal positive electrode material can further improve the capacitance performance of the composite positive electrode.
[0061] Please refer to FIG. 6A to FIG. 6C . FIG. 6A to FIG. 6C The following table 1 shows the discharge capacity and capacity retention rate of the button batteries made in the second example, the third example and the first comparative example at the 1st cycle and the 100th cycle. The positive electrode of the button battery is the composite positive electrode of the second example, the third example and the first comparative example, and the negative electrode is lithium metal. FIG. 6A to FIG. 6Cas shown in Table 1. The discharge capacity of the second exemplary embodiment at the 1st cycle is 192 mAh / g, and at the 100th cycle is 118.8 mAh / g, with a capacitance retention rate of 61.9%. The discharge capacity of the third exemplary embodiment at the 1st cycle is 204.9 mAh / g, and at the 100th cycle is 164.5 mAh / g, with a capacitance retention rate of 80.3%. The discharge capacity of the first comparative example at the 1st cycle is 171.5 mAh / g, and the discharge capacity starts to drop sharply since the 4th cycle, and is less than 0.2 mAh / g at the 8th cycle. It can be seen that, compared with the composite positive electrode prepared by dry mixing, the composite positive electrode prepared by wet mixing with an alcohol solvent has higher initial capacitance performance and cycling performance. In addition, compared with the second exemplary embodiment with a positive electrode material composition of Li[Ni 0.83 Co 0.12 Mn 0.05 O2, the third exemplary embodiment with a positive electrode material composition of Li[Ni 0.88 Co 0.06 Mn 0.06 O2 has better capacitance performance and cycling performance. In other words, the positive electrode material with a composition of Li[Ni a Co b Mn c O2 and 0.85 < a ≤ 1 can further improve the capacitance performance and cycling performance of the composite positive electrode.
[0062]
[0063] Table 1
[0064] Fourth Exemplary Embodiment:
[0065] The preparation method of the fourth exemplary embodiment is substantially the same as that of the first exemplary embodiment, except that in the fourth exemplary embodiment, the composition of the solid electrolyte is Li3InCl 5.19 F 0.81 .
[0066] Fifth Exemplary Embodiment:
[0067] The preparation method of the fifth exemplary embodiment is substantially the same as that of the first exemplary embodiment, except that in the fifth exemplary embodiment, the composition of the solid electrolyte is Li3InCl 4.77 F 1.23 .
[0068] Sixth Exemplary Embodiment:
[0069] The preparation method of the sixth exemplary embodiment is substantially the same as that of the first exemplary embodiment, except that in the sixth exemplary embodiment, the composition of the solid electrolyte is Li3InCl 4.35 F 1.65 .
[0070] Table 2 below shows the discharge capacity of the button cells made in the first, fourth, fifth and sixth examples at the 1st and 45th cycles, respectively. The positive electrode of the button cell is the positive electrode material of the first, fourth, fifth and sixth examples, respectively, and the negative electrode is lithium metal. The voltage window is 2.5V to 4.4V, the charge and discharge rate (C-rate) is 0.1C, and the constant current (CC) mode is used for charging, and the constant current constant voltage (CCCV) mode is used for discharging. The constant current constant voltage mode of discharge is to maintain the current constant during the discharge process, and then maintain the voltage constant until the discharge is completed after reaching the upper limit voltage. The temperature condition of the charge and discharge test is 55°C. As shown in Table 2, at the first cycle, the discharge capacity of the fifth example with a chlorine:fluorine ratio of 4.77:1.23 is 196.18 mAh / g, slightly higher than the discharge capacity of the first example, while the discharge capacity of the fourth example with a chlorine:fluorine ratio of 5.19:0.81 is 189.49 mAh / g, slightly lower than the discharge capacity of the first example, but the difference is not obvious. At the 45th cycle, the discharge capacity of the fourth example is 160.21 mAh / g, which is 8.31% higher than the discharge capacity of the first example of 147.91 mAh / g; the discharge capacity of the fifth example is 166.90 mAh / g, which is 12.83% higher than the discharge capacity of the first example of 147.91 mAh / g. It can be seen that the use of a solid electrolyte composed of chlorine and fluorine can significantly improve the discharge capacity of the positive electrode material, and a solid electrolyte with a chlorine:fluorine ratio between 5.3:0.7 and 4.5:1.5 has a better effect.
[0071]
[0072] Table 2
[0073] Table 3 below shows the discharge capacity retention rates of the button cells prepared in the first, fourth, fifth and sixth examples at the 45th cycle. As shown in Table 3, at the 45th cycle, the discharge capacity retention rate of the fourth example is 84.55%, which is 10.31% higher than the discharge capacity retention rate of 76.65% of the first example; the discharge capacity retention rate of the fifth example is 85.07%, which is 10.98% higher than the discharge capacity retention rate of 76.65% of the first example; the discharge capacity retention rate of the sixth example is 78.44%, which is 2.34% higher than the discharge capacity retention rate of 76.65% of the first example. It can be seen that the use of a solid electrolyte composed of chlorine and fluorine can significantly improve the discharge capacity retention rate of the positive electrode material, and the solid electrolyte with a chlorine:fluorine ratio between 5.3:0.7 and 4.5:1.5 has a better effect.
[0074] Discharge capacity retention rate at the 45th cycle First example 76.65% Fourth Example 84.55% Fifth Example 85.07% Sixth Example 78.44%
[0075] Table 3
[0076] In summary, the purpose of this case is to provide a method for preparing a composite positive electrode. The method for preparing a composite positive electrode includes the following steps. First, a positive electrode material, a solid electrolyte and an alcohol solvent are mixed to form a slurry. Then, the slurry is heat-treated to form a composite positive electrode. Compared with dry mixing, wet mixing is low-cost, easy to control, and can improve the solid dispersion of the composite positive electrode. Furthermore, the solid electrolyte is dissolved in an alcohol solvent and uniformly mixed with the positive electrode material, so that in-situ synthesis (In-situ synthesis) can be achieved on the surface of the positive electrode material particles in the subsequent heat treatment, thereby forming a composite positive electrode particle with a uniform core-shell structure and improving the electrochemical performance. Wet mixing by alcohol solvents can also eliminate the negative impact of moisture on the composite positive electrode, resulting in a composite positive electrode with a low impurity phase. Before heat treatment, the slurry is, for example, coated on a carrier and rolled to form. The carrier is, for example, an anti-adhesive film, which is conducive to stripping after forming. The slurry is further coated between two carriers for roll forming, and the carriers are respectively an anti-adhesive film and a current collector, so that a current collector with a composite positive electrode can be directly obtained after heat treatment. The heat treatment temperature is, for example, between 160°C and 200°C, which has low energy consumption, saves manufacturing costs and has environmental benefits.
[0077] This case may be modified in various ways by those skilled in the art, but all of them will not deviate from the protection sought by the attached claims.
Claims
1. A method for preparing a composite positive electrode, comprising the steps of: (a) Provide a positive electrode material, a solid electrolyte, a conductive carbon, and an alcohol solvent, wherein the positive electrode material includes a plurality of first particles, and the composition of the positive electrode material is Li[Ni a Co b Mn c Al d O2, a + b + c + d = 1, 0.8 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1, wherein the composition of the solid electrolyte is Li3InCl x F y , and x + y ≤ 6, 0 ≤ x ≤ 6, 0 ≤ y ≤ 3; (b) mixing the positive electrode material, the solid electrolyte, the conductive carbon and the alcohol solvent to form a first slurry; (c) mixing the first slurry and a binder to form a second slurry; and (d) heat treating the second slurry to remove the alcohol solvent to form the composite positive electrode, wherein the composite positive electrode includes a plurality of second particles, each of the plurality of second particles includes one of the plurality of first particles and the solid electrolyte, and the solid electrolyte covers the one of the plurality of first particles, wherein the conductive carbon and the binder are uniformly distributed between the plurality of second particles. 2 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the particle size of the first particles is between 0.5 μm and 30 μm. 3 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the positive electrode material comprises a single crystal positive electrode material.
4. The method for preparing a composite positive electrode according to claim 1, wherein 0.85 <a≤1。 5 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the alcohol solvent comprises ethanol. 6 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the second slurry is heat-treated after being formed. 7 . The method for preparing a composite positive electrode as claimed in claim 6 , wherein the second slurry is formed on a first carrier, and the first carrier comprises a current collector or an anti-adhesion material. 8 . The method for preparing a composite positive electrode as claimed in claim 7 , wherein the first carrier comprises two first carriers, and the second slurry is formed between the two first carriers. 9 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the second slurry is heat-treated on a second carrier, and the second carrier comprises glass or metal. 10 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the temperature of the heat treatment is between 160° C. and 200° C. 11 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the heat treatment time is between 10 minutes and 180 minutes. 12 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the heat treatment is performed in a non-oxidizing atmosphere. 13 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the conductive carbon comprises carbon black, carbon nanotube or carbon fiber. 14 . The method for preparing a composite positive electrode as claimed in claim 1 , wherein the binder comprises polytetrafluoroethylene.
Citation Information
Cited By
High-specific-energy lithium-rich manganese-based positive electrode slurry for solid-state battery, and preparation method and application thereof
CN121565822A